LATE HOLOCENE PALAEOCEANOGRAPHY IN VAN MIJENFJORDEN, SVALBARD - Hald M.; Dahlgren T.; Olsen T.-E.; Lebesbye E. (My University, 2001)
Based on detailed stratigraphical analysis of sediment cores spanning the last ca. 4000 calendar years, we reconstruct the palaeoceanograhic changes in the fiord Van Mijenfjorden, western Svalbard. Benthic foraminiferal δ18O indicate a gradual reduction in bottom water salinities between 2200 BC and 500 BC. This reduction was probably mainly a function of reduced inflow of oceanic water to the fiord, due to isostatic shallowing of the outer fiord sill. Stable salinity conditions prevailed between 500 BC and. 1300 AD. After the onset of a major glacial surge of the tidewater Paulabreen (Paula Glacier) system (PGS) around 1300 AD, there was a foraminiferal faunal change towards glacier proximal conditions, associated with a slight bottom water salinity depletion. During a series of glacial surges occuring from 1300 AD up the present salinity in the fiord has further decreased, corresponding to a δ18O depletion of 0.5 %o. This salinity decrease corresponds to the period when the PGS lost an equivalent of 30 – 40 % of its present ice volume, mainly through calving in the fiord.
Keywords: Holocene; palaeoceanography; Svalbard; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен